Modified calcium-based montmorillonite as well as preparation method and application thereof

Calcium montmorillonite is modified by treatment of acid solution and silicon-containing solution to form modified calcium montmorillonite with a high mesoporous specific surface area, which solves the problems of short service life and environmental pollution in the aromatic deolefining reaction, and achieves the dual effects of long service life and environmental protection.

CN119929814APending Publication Date: 2025-05-06CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311464898.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

In the prior art, white clay has a short service life in aromatic deolefining reaction, and mining white clay will cause environmental damage. The inactivated white clay is harmful to human health and cannot be recycled, resulting in secondary environmental pollution.

Method used

Calcium montmorillonium was modified by acid solution and silicon-containing solution treatment method, and its interlayer structure was changed to form modified calcium montmorillonium with a high mesoporous specific surface area.

Benefits of technology

Modified calcium-based montmorillonite has a long service life in aromatic deolefining reaction, and is more environmentally friendly, and will not pose a threat to human health and avoid secondary pollution of the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004533301190000011
    Figure HDA0004533301190000011
  • Figure HDA0004533301190000012
    Figure HDA0004533301190000012
  • Figure HDA0004533301190000013
    Figure HDA0004533301190000013
Patent Text Reader

Abstract

The invention discloses modified calcium-based montmorillonite as well as a preparation method and application thereof, on an XRD (X-Ray Diffraction) diagram of the modified calcium-based montmorillonite, a diffraction peak appears at 2theta of 25.2 to 25.6 degrees, and a diffraction peak appears at 27.1 to 27.6 degrees; the preparation method comprises the following steps: carrying out acid treatment on calcium-based montmorillonite, filtering to take a solid phase, and carrying out organic silicon treatment on the solid phase. Wherein the modified calcium-based montmorillonite with part of XRD diffraction peaks changed can be obtained by adopting an acid solution and silicon-containing solution treatment method, the interlayer structure of the modified calcium-based montmorillonite is changed, part of crystal faces have higher probability of being exposed outside, and the formation of the high mesoporous specific surface area is also promoted by the change of the interlayer structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of modified montmorillonite, and in particular relates to a modified calcium-based montmorillonite and a preparation method and application thereof. Background Art

[0002] Aromatics is the basic raw material of the petrochemical industry, and it mainly comes from aromatics complexes. Aromatic products after catalytic reforming reactions contain a certain amount of olefin impurities. Olefins are active in nature and are not only easy to polymerize to form colloids, but may also react with other components to generate non-ideal components, thus having a significant impact on the quality of aromatic products.

[0003] On the other hand, some petrochemical processes, such as xylene adsorption separation, are particularly sensitive to olefins. Even if the content of olefin impurities is only a few parts per million, it will have a very adverse effect on the process. In order to obtain qualified chemical raw materials and ensure the smooth progress of subsequent processes, there are refining processes after reforming, aromatics extraction, isomerization, and toluene disproportionation to remove trace olefin impurities.

[0004] White clay has an acidic center and has a certain catalytic superposition ability and pore adsorption ability under high-pressure liquid phase and 150-200°C conditions. It can cause trace olefins contained in the reforming oil to undergo hydrocarbonization, polymerization and other reactions to generate high-boiling point compounds, which are then adsorbed by the white clay or removed in subsequent separation processes.

[0005] Mining clay will cause permanent damage to the environment. In addition, the deactivated aromatic clay cannot be recycled because it is very harmful to human health and can only be disposed of by landfill, which causes serious secondary pollution to the environment. As environmental awareness continues to increase, this issue has received more and more attention from the country and the public, and production companies are in urgent need of catalytic deolefination technology that can solve these problems.

[0006] The biggest advantage of using kaolin as a refining agent in the aromatics deolefination unit is its low price. If the performance of kaolin can be greatly improved, its cost-effectiveness and technical economy will still be strong.

[0007] The conventional preparation method of activated clay includes acid activation, centrifugal separation, multiple washing, neutralization, drying and crushing, etc. The activated clay prepared by this method has a short service life in the aromatic deolefination reaction, so metal modification processes such as Zn and Al are usually added to extend the service life. Summary of the invention

[0008] In order to overcome the problems existing in the prior art, the present invention provides a modified calcium-based montmorillonite and a preparation method and application thereof, wherein a modified calcium-based montmorillonite with some XRD diffraction peaks changed can be obtained by treating with an acid solution or a silicon-containing solution. After the modification, the interlayer structure of the calcium-based montmorillonite changes, and some crystal faces are more likely to be exposed to the outside. The change in the interlayer structure also promotes the formation of a high mesoporous specific surface area.

[0009] The first aspect of the present invention is to provide a modified calcium-based montmorillonite, in which 2theta diffraction peaks appear at 25.2°-25.6° and 27.1°-27.6° in an XRD diagram.

[0010] In the XRD diagram of the modified calcium-based montmorillonite, the diffraction peak intensity near 4° to 7° is reduced by more than 80% or disappears, and is in a diffuse state. The intensity reduction is based on the unmodified calcium-based montmorillonite, and is reduced by more than 80% or disappears compared with the unmodified montmorillonite. For example, it is reduced by 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98% or 100%.

[0011] The total specific surface area of ​​the modified calcium-based montmorillonite is greater than 250 m 2 / g, preferably 250 to 350 m 2 / g.

[0012] The surface area of ​​the modified calcium-based montmorillonite is 180 to 280 m 2 / g, preferably 180 to 250 m 2 / g.

[0013] Taking the total specific surface area of ​​the modified calcium-based montmorillonite as 100%, the external surface area accounts for more than 70%, for example, 70% to 80%.

[0014] The second aspect of the present invention is to provide a method for preparing a modified calcium-based montmorillonite, preferably for preparing the modified calcium-based montmorillonite described in the first aspect of the present invention, the preparation method comprising: acid-treating the calcium-based montmorillonite, filtering out a solid phase, and treating the solid phase with silicone.

[0015] The acid treatment comprises: mixing the calcium-based montmorillonite with an acidic reagent, adjusting the pH to -1 to 3, heating and stirring; preferably, the acidic reagent is selected from an acid solution, wherein the acid is selected from at least one of sulfuric acid, nitric acid and hydrochloric acid; more preferably, in the acid treatment, the stirring is performed at 80°C to 130°C for 1 to 10 hours.

[0016] The organosilicon treatment comprises: mixing the solid phase with water, adding organosilicon, and stirring;

[0017] Preferably, the weight ratio of water to calcium-based montmorillonite is (1-4):1, preferably (2-3):1;

[0018] Preferably, the weight ratio of the organosilicon to the calcium-based montmorillonite is (0.02-0.5):1, preferably (0.05-0.2):1.

[0019] The organosilicon is selected from at least one of polyether-modified silicone oil and tetraalkyl silicate;

[0020] Preferably, the polyether in the polyether-modified silicone oil is selected from at least one of glycerol polyoxyethylene polyoxypropylene ether and acryl alcohol polyether; and / or the viscosity of the polyether in the polyether-modified silicone oil is 200-2000 cst; and / or the alkyl silicate is selected from at least one of tetramethyl silicate, tetraethyl silicate, tetrapropyl silicate and tetrabutyl silicate.

[0021] After the organosilicon treatment, filtering and calcination are performed, preferably, calcination is performed at 250° C. to 450° C. in an air atmosphere.

[0022] The third aspect of the present invention is to provide the use of the modified calcium-based montmorillonite in aromatic deolefination catalysts.

[0023] The fourth aspect of the present invention is to provide an aromatic deolefination catalyst, which comprises the modified calcium-based montmorillonite.

[0024] The fifth aspect of the present invention is to provide a method for deolefination of aromatics, comprising: contacting an aromatic material with the modified calcium-based montmorillonite or the aromatic deolefination catalyst to remove olefins from the aromatic material;

[0025] Preferably, the contact reaction conditions include: temperature of 150-270°C, pressure of 0.6MPa-3.0MPa, feed weight space velocity of 2-8h -1 .

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) A modified calcium-based montmorillonite having a high mesoporous specific surface area and a high proportion of the surface area in the total surface area is provided;

[0028] (2) A method for preparing calcium-based montmorillonite with a high mesoporous specific surface area is provided, wherein the modified calcium-based montmorillonite with some XRD diffraction peaks changed can be obtained by treating with an acid solution or a silicon-containing solution;

[0029] (3) Compared with the calcium-based montmorillonite treated only with acid, the modified calcium-based montmorillonite prepared by this method has the advantage of long service life in the aromatic deolefination reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD patterns of the modified calcium-based montmorillonite obtained in Example 1 of the present invention (upper curve) and the raw calcium-based montmorillonite in Example 1 (lower curve) are shown;

[0031] Figure 2 Show Figure 1 Local magnification within the range of 4 to 10°;

[0032] Figure 3 Show Figure 1 A local magnified image within the range of 25 to 30°. DETAILED DESCRIPTION

[0033] One of the purposes of the present invention is to provide a modified calcium-based montmorillonite, in which diffraction peaks appear at 25.2° to 25.6° (e.g., 25.2°, 25.3°, 25.4°, 25.5° or 25.6°) and 27.1° to 27.6° (e.g., 27.1°, 27.2°, 27.3°, 27.4°, 27.5° or 27.6°) in its XRD diagram. This indicates that after modification, the interlayer structure of the calcium-based montmorillonite has changed, and some crystal faces have a higher probability of being exposed. The change in the interlayer structure is also the main reason why the modified calcium-based montmorillonite has a high mesoporous specific surface area.

[0034] In a preferred embodiment, in the XRD diagram of the modified calcium-based montmorillonite, the diffraction peak intensity near 4° to 7° is reduced by more than 80% (dispersed) or disappears, which also indicates that the interlayer structure and crystal spacing of the modified calcium-based montmorillonite have changed significantly.

[0035] In a preferred embodiment, on the XRD diagram of the modified calcium-based montmorillonite, two diffraction peaks appear at 27.1° to 27.6° (preferably 27.1° to 27.5°, for example, any two of 27.1°, 27.2°, 27.3°, 27.4°, 27.5°, and 27.6°).

[0036] In a preferred embodiment, the total specific surface area of ​​the modified calcium-based montmorillonite is greater than 250 m 2 / g, preferably 250 to 350 m 2 / g, for example, 250m 2 / g, 260m 2 / g, 280m 2 / g、300m 2 / g, 320m 2 / g, 340m 2 / g or 350m 2 Any point value or any range of two point values ​​in / g.

[0037] In a preferred embodiment, the surface area of ​​the modified calcium-based montmorillonite is 180 to 280 m 2 / g, preferably 180 to 250 m 2 / g, for example, 180m 2 / g, 200m 2 / g, 220m 2 / g, 240m 2 / g, 260m 2 / g or 280m 2 Any point value or any range of two point values ​​in / g.

[0038] In a preferred embodiment, based on 100% of the total specific surface area of ​​the modified calcium-based montmorillonite, its external surface area accounts for more than 70%, for example, 70% to 80%, and more preferably, any point value among 70%, 75%, 80%, 85%, 90%, or a range consisting of any two points.

[0039] In a preferred embodiment, the modified calcium-montmorillonite is obtained by treating calcium-montmorillonite with acid and modifying it with organosilicon.

[0040] The second object of the present invention is to provide a method for preparing modified calcium-based montmorillonite, preferably for preparing the modified calcium-based montmorillonite described in one of the objects of the present invention, the preparation method comprising: sequentially subjecting the calcium-based montmorillonite to acid treatment, filtration and silicone treatment.

[0041] The calcium-based montmorillonite is treated with acid, the solid phase is filtered out, and the solid phase is treated with organic silicon.

[0042] In a preferred embodiment, the acid treatment comprises: mixing the calcium-based montmorillonite with an acidic agent, adjusting the pH to -1 to 3 (for example, any point value among -1, 0, 1, 2 or 3 or a range consisting of any two points), heating and stirring.

[0043] In a further preferred embodiment, during the acid treatment, the pH is adjusted to -1 to 1.

[0044] Among them, the inventors found after a lot of experimental studies that the modification effect when the pH is controlled at -1 to 3 (preferably -1 to 1) during acid treatment is significantly better than the modification effect when the pH is controlled at higher than 4 (for example, 5 to 8).

[0045] In a further preferred embodiment, during the acid treatment, the stirring is carried out at 80°C to 130°C for 1 to 10 h, preferably at 90°C to 120°C for 2 to 8 h, for example, at 80°C, 90°C, 100°C, 110°C, 120°C or 130°C for 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0046] In a preferred embodiment, the acidic reagent is selected from an acid solution (aqueous solution), wherein the acid is selected from at least one of sulfuric acid, nitric acid and hydrochloric acid.

[0047] In a further preferred embodiment, the concentration of the acid solution is 0.1-10M, preferably 0.5-5M, for example, any point value among 0.1M, 0.2M, 0.5M, 0.8M, 1M, 1.5M, 2M, 2.5M, 3M, 5M, 6M, 8M or 10M or a range consisting of any two points.

[0048] In a preferred embodiment, the organosilicon treatment comprises: mixing the filtered solid phase with water, adding organosilicon, and stirring (preferably 2 to 50 hours, more preferably 6 to 36 hours, for example, any point value among 2h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h, 40h, 42h, 45h, 48h or 50h, or a range consisting of any two points).

[0049] In a further preferred embodiment, the weight ratio of water to calcium-based montmorillonite is (1-4):1, preferably (2-3):1, for example, any point value among 1:1, 2:1, 3:1 or 4:1, or a range consisting of any two points.

[0050] In a further preferred embodiment, the weight ratio of the organosilicon to the calcium-based montmorillonite is (0.02-0.5):1, preferably (0.05-0.2):1, for example, any point value among 0.02:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1 or 0.5:1, or a range consisting of any two points.

[0051] In a preferred embodiment, the organosilicon is selected from at least one of polyether-modified silicone oil and tetraalkyl silicate.

[0052] Among them, after a large number of experimental studies, the inventors found that the effect of organosilicon modification using polyether-modified silicone oil is better than that of tetraalkyl silicate. In addition, the effects of modification using polyether-modified silicone oil and tetraalkyl silicate are better than those using silane coupling agent. The role of organosilicon in the present invention is to support silicon oxide into the interlayer of calcium-based montmorillonite, increase its mesoporous specific surface area, and increase the pore size. Polyether-modified silicone oil has good water solubility, high stability in water, and uniform modification effect during the treatment process. The tetraalkyl silicate aqueous solution will slowly decompose into silicon oxide compounds during the pillaring process, so the modification effect is second. There are many restrictions on the use conditions of silane coupling agents. For example, except for aminoalkylsilane, solutions prepared by other silane coupling agents need to add acetic acid as a hydrolysis catalyst, and the pH value is strictly controlled. Long-chain alkyl and phenyl silanes are not suitable for use in aqueous solutions due to their poor stability. Chlorosilane and ethoxysilane are accompanied by severe condensation reactions during hydrolysis, and aminoalkylsilane is usually more irritating. Therefore, the comprehensive modification effect of silane coupling agent is not good.

[0053] In a further preferred embodiment, the polyether in the polyether-modified silicone oil is selected from at least one of glycerol polyoxyethylene polyoxypropylene ether and propylene alcohol polyether; and / or the viscosity of the polyether in the polyether-modified silicone oil is 200 to 2000 cst, for example, any point value among 200 cst, 500 cst, 800 cst, 1000 cst, 1200 cst, 1500 cst, 1800 cst or 2000 cst, or a range consisting of any two points.

[0054] In a further preferred embodiment, the alkyl silicate is selected from at least one of tetramethyl silicate, tetraethyl silicate, tetrapropyl silicate and tetrabutyl silicate.

[0055] In a preferred embodiment, filtering and calcination are performed after the organosilicon treatment.

[0056] In a further preferred embodiment, a solid phase is taken after the filtration, and then the solid phase is calcined.

[0057] In a further preferred embodiment, the solid phase is first dried (e.g., baked) and then calcined in an air atmosphere at 250°C to 450°C (e.g., any point value or a range consisting of any two points among 250°C, 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, 420°C or 450°C) to obtain the modified calcium-based montmorillonite.

[0058] The third object of the present invention is to provide the use of the modified calcium-based montmorillonite described in the first object of the present invention or the modified calcium-based montmorillonite obtained by the preparation method described in the second object of the present invention in aromatic deolefination catalysts.

[0059] A fourth object of the present invention is to provide an aromatic deolefination catalyst, which comprises the modified calcium-based montmorillonite described in one of the objects of the present invention or the modified calcium-based montmorillonite obtained by the preparation method described in the second object of the present invention.

[0060] The fifth object of the present invention is to provide a method for deolefination of aromatics, comprising: contacting an aromatic material with the modified calcium-based montmorillonite described in the first object of the present invention or the modified calcium-based montmorillonite obtained by the preparation method described in the second object of the present invention or the aromatic deolefination catalyst described in the fourth object of the present invention to remove olefins from the aromatic material.

[0061] In a preferred embodiment, the contact reaction conditions include: temperature of 150-270°C, pressure of 0.6MPa-3.0MPa, feed weight space velocity of 2-8h -1 .

[0062] For example, the contact reaction conditions include: a temperature of any point value or a range consisting of any two points among 150°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C or 270°C; a pressure of any point value or a range consisting of any two points among 0.6MPa, 0.8MPa, 1MPa, 1.2MPa, 1.4MPa, 1.6MPa, 1.8MPa, 2MPa, 2.2MPa, 2.4MPa, 2.6MPa, 2.8MPa or 3.0MPa; a feed weight space velocity of 2: -1 , 4 o'clock -1 , 6 o'clock -1 or 8 o'clock -1 Any point value or any range of two point values ​​in .

[0063] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0064] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0065] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0066] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0067] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0068] The polyether-modified silicone oil (viscosity 1000 cst) was purchased from MacLean's reagent.

[0069] [Example 1]

[0070] 50 g of calcium-based montmorillonite was added to 100 ml of 1.8 M sulfuric acid solution, the pH was adjusted to -0.5, the temperature was raised to 100 ° C while stirring, and the filter cake i was obtained by centrifugal filtration after 4 hours of treatment; the filter cake i was dispersed in 100 ml of water, 4 g of polyether-modified silicone oil (viscosity 1000 cst) was slowly added, the mixture was stirred for 12 hours and then centrifuged, dried at 120 ° C, and calcined at 400 ° C in an air atmosphere for 3 hours to obtain modified calcium-based montmorillonite MTT-1.

[0071] Compared with calcium-based montmorillonite, MTT-1 has new diffraction peaks at 25.4°, 27.3° and 27.4° at 2theta, and the intensity of the diffraction peak near 4° to 7° is reduced (reduced by 83% compared with the calcium-based montmorillonite raw material), with a total specific surface area of ​​279m 2 / g, with an external surface area of ​​215m 2 / g, and the surface area accounts for 77%.

[0072] MTT-1 was tableted, crushed, and 5 grams of 20-40 mesh were taken to carry out the non-hydrogenation deolefination test of reformed oil in a fixed bed reactor. The raw material bromine index was 1140 mg Br / 100 g oil. The reaction temperature was 150°C, the reaction pressure was 2.0 MPa, and the feed weight space velocity was 5.0 -1 Taking the export bromine index of 200 mg Br / 100 g oil as the standard, the reaction stability reaches 252 hours.

[0073] [Example 2]

[0074] 50 g of calcium-based montmorillonite was added with 100 ml of 1.8 M sulfuric acid solution, the pH was adjusted to -0.5, the temperature was raised to 100 ° C while stirring, and the filter cake i was obtained by centrifugation after treatment for 4 hours; the filter cake i was dispersed in 100 ml of water, 4 g of tetraethyl silicate was slowly added, the mixture was stirred for 12 hours, and then centrifuged, dried at 120 ° C, and calcined at 400 ° C in air atmosphere for 3 hours to obtain modified calcium-based montmorillonite MTT-2.

[0075] Compared with calcium-based montmorillonite, MTT-2 has new diffraction peaks at 25.5°, 27.4° and 27.5° at 2theta, and the intensity of the diffraction peak near 4° to 7° is reduced (reduced by 80% compared with the calcium-based montmorillonite raw material), with a total specific surface area of ​​253m 2 / g, with an external surface area of ​​191m 2 / g, and the surface area accounts for 75%.

[0076] MTT-2 was tableted, crushed, and 5 grams of 20-40 mesh were taken to carry out the reforming oil non-hydrogenation deolefination test in a fixed bed reactor. The raw material bromine index was 1140 mg Br / 100 g oil. The reaction temperature was 150°C, the reaction pressure was 2.0 MPa, and the feed weight space velocity was 5.0 h. -1 Taking the export bromine index of 200 mg Br / 100 g oil as the standard, the reaction stability reaches 216 hours.

[0077] [Example 3]

[0078] 50 g of calcium-based montmorillonite was added to 150 ml of 1.5 M sulfuric acid solution, the pH was adjusted to -0.42, the temperature was raised to 110°C under stirring, and the filter cake i was obtained by centrifugal filtration after 2 hours of treatment; the filter cake i was dispersed in 150 ml of water, 6 g of polyether-modified silicone oil (viscosity 1000 cst) was slowly added, the mixture was stirred for 12 hours, centrifuged, dried at 120°C, and calcined at 450°C in an air atmosphere for 3 hours to obtain modified calcium-based montmorillonite MTT-3.

[0079] Compared with calcium-based montmorillonite, MTT-3 has new diffraction peaks at 25.3°, 27.2° and 27.3° at 2theta, and the intensity of the diffraction peak near 4° to 7° is reduced (reduced by 87% compared with the calcium-based montmorillonite raw material), with a total specific surface area of ​​292m 2 / g, with an external surface area of ​​223m 2 / g, and the surface area accounts for 76%.

[0080] MTT-3 was tableted, crushed, and 5 grams of 20-40 mesh were taken to carry out the reforming oil non-hydrogenation deolefination test in a fixed bed reactor. The raw material bromine index was 1140 mg Br / 100 g oil. The reaction temperature was 150°C, the reaction pressure was 2.0 MPa, and the feed weight space velocity was 5.0 -1Taking the export bromine index of 200 mg Br / 100 g oil as the standard, the reaction stability reaches 288 hours.

[0081] [Example 4]

[0082] 50 g of calcium-based montmorillonite was added with 100 ml of 1.95 M sulfuric acid solution, the pH was adjusted to -0.55, the temperature was raised to 95°C under stirring, and the filter cake i was obtained by centrifugation after treatment for 4 hours; the filter cake i was dispersed in 100 ml of water, 7 g of tetraethyl silicate was slowly added, the mixture was stirred for 12 hours, and then centrifuged, dried at 120°C, and calcined at 400°C in air atmosphere for 3 hours to obtain modified calcium-based montmorillonite MTT-4.

[0083] Compared with calcium-based montmorillonite, MTT-4 has new diffraction peaks at 25.4°, 27.3° and 27.4° at 2theta, and the intensity of the diffraction peak near 4° to 7° is reduced (reduced by 82% compared with the calcium-based montmorillonite raw material), with a total specific surface area of ​​277m 2 / g, with an external surface area of ​​198m 2 / g, and the surface area accounts for 71%.

[0084] MTT-4 was tableted, crushed, and 5 grams of 20-40 mesh were taken to carry out the non-hydrogenation deolefination test of reforming oil in a fixed bed reactor. The raw material bromine index was 1140 mg Br / 100 g oil. The reaction temperature was 150°C, the reaction pressure was 2.0 MPa, and the feed weight space velocity was 5.0 -1 Taking the export bromine index of 200 mg Br / 100 g oil as the standard, the reaction stability reaches 228 hours.

[0085] [Example 5]

[0086] 50 g of calcium-based montmorillonite was added to 150 ml of 1.5 M sulfuric acid solution, the pH was adjusted to -0.42, the temperature was raised to 100 ° C while stirring, and the filter cake i was obtained by centrifugal filtration after treatment for 3 hours; the filter cake i was dispersed in 150 ml of water, 9 g of polyether-modified silicone oil (viscosity 1000 cst) was slowly added, the mixture was stirred for 12 hours, the mixture was centrifuged, the mixture was dried at 120 ° C, and the mixture was calcined at 450 ° C in an air atmosphere for 5 hours to obtain modified calcium-based montmorillonite MTT-5.

[0087] Compared with calcium-based montmorillonite, MTT-5 has new diffraction peaks at 25.2°, 27.1° and 27.2° at 2theta, and the intensity of the diffraction peak near 4° to 7° is reduced (reduced by 90% compared with the calcium-based montmorillonite raw material), with a total specific surface area of ​​328m 2 / g, with an external surface area of ​​233m 2 / g, and the surface area accounts for 71%.

[0088] MTT-5 was tableted, crushed, and 5 grams of 20-40 mesh were taken to carry out the reforming oil non-hydrogenation deolefination test in a fixed bed reactor. The raw material bromine index was 1140 mg Br / 100 g oil. The reaction temperature was 150°C, the reaction pressure was 2.0 MPa, and the feed weight space velocity was 5.0 -1 Taking the export bromine index of 200 mg Br / 100 g oil as the standard, the reaction stability reaches 312 hours.

[0089] [Comparative Example 1]

[0090] 0.3 g of sulfuric acid was added to 1000 ml of water, and after mixing evenly, 150 ml was taken out, and 50 g of calcium montmorillonite was added to adjust the pH to 5. The mixture was heated to 100°C while stirring, and centrifuged after treating for 4 hours to obtain filter cake i; filter cake i was dispersed in 100 ml of water, and 4 g of polyether-modified silicone oil (viscosity 1000 cst) was slowly added. The mixture was stirred for 12 hours and then centrifuged. The mixture was dried at 120°C and calcined at 400°C in air for 3 hours to obtain modified calcium montmorillonite DMTT-1.

[0091] The diffraction peak angle of the XRD spectrum of DMTT-1 is consistent with that of calcium-based montmorillonite, and the total specific surface area is 92m 2 / g, with an external surface area of ​​55m 2 / g, and the surface area accounts for 60%.

[0092] DMTT-1 was tableted, crushed, and 5 grams of 20-40 mesh were taken to carry out the reforming oil non-hydrogenation deolefination test in a fixed bed reactor. The raw material bromine index was 1140 mg Br / 100 g oil. The reaction temperature was 150°C, the reaction pressure was 2.0 MPa, and the feed weight space velocity was 5.0 h. -1 , taking the export bromine index of 200 mg Br / 100 g oil as the standard, the reaction stability reaches 18 hours.

[0093] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A modified calcium-based montmorillonite, in which 2theta diffraction peaks appear at 25.2°-25.6° and 27.1°-27.6° in its XRD diagram.

2. The modified calcium-based montmorillonite according to claim 1, characterized in that: In the XRD diagram of the modified calcium-based montmorillonite, the intensity of the diffraction peak near 4° to 7° is reduced by more than 80% or disappears; and / or two diffraction peaks appear at 27.1° to 27.6°.

3. The modified calcium-based montmorillonite according to claim 1, characterized in that: The total specific surface area of ​​the modified calcium-based montmorillonite is greater than 250 m 2 / g, preferably 250 to 350 m 2 / g.

4. The modified calcium-based montmorillonite according to claim 1, characterized in that: The surface area of ​​the modified calcium-based montmorillonite is 180 to 280 m 2 / g, preferably 180 to 250 m 2 / g.

5. The modified calcium-based montmorillonite according to any one of claims 1 to 4, characterized in that: Taking the total specific surface area of ​​the modified calcium-based montmorillonite as 100%, the proportion of the external surface area is higher than 70%.

6. A method for preparing a modified calcium-based montmorillonite, preferably for preparing the modified calcium-based montmorillonite according to any one of claims 1 to 5, the method comprising: The calcium-based montmorillonite is treated with acid, a solid phase is collected by filtration, and the solid phase is treated with organic silicon.

7. The preparation method according to claim 6, characterized in that: The acid treatment comprises: mixing the calcium-based montmorillonite with an acidic reagent, adjusting the pH to 1-3, heating and stirring; preferably, the acidic reagent is selected from an acid solution, wherein the acid is selected from at least one of sulfuric acid, nitric acid and hydrochloric acid; more preferably, in the acid treatment, the stirring is performed at 80°C to 130°C for 1 to 10 hours.

8. The preparation method according to claim 6, characterized in that: The organosilicon treatment comprises: mixing the solid phase with water, adding organosilicon, and stirring; Preferably, the weight ratio of water to calcium-based montmorillonite is (1-4):1, preferably (2-3):1; Preferably, the weight ratio of the organosilicon to the calcium-based montmorillonite is (0.02-0.5):1, preferably (0.05-0.2):

1.

9. The preparation method according to claim 6, characterized in that: The organosilicon is selected from at least one of polyether-modified silicone oil and tetraalkyl silicate; Preferably, the polyether in the polyether-modified silicone oil is selected from at least one of glycerol polyoxyethylene polyoxypropylene ether and acryl alcohol polyether; and / or the viscosity of the polyether in the polyether-modified silicone oil is 200-2000 cst; and / or the alkyl silicate is selected from at least one of tetramethyl silicate, tetraethyl silicate, tetrapropyl silicate and tetrabutyl silicate.

10. The preparation method according to any one of claims 6 to 9, characterized in that: After the organosilicon treatment, filtering and calcination are performed, preferably, calcination is performed at 250° C. to 450° C. in an air atmosphere.

11. Use of the modified calcium-based montmorillonite according to any one of claims 1 to 5 or the modified calcium-based montmorillonite obtained by the preparation method according to any one of claims 6 to 10 in aromatic deolefination catalysts.

12. An aromatic deolefination catalyst, comprising the modified calcium-based montmorillonite according to any one of claims 1 to 5 or the modified calcium-based montmorillonite obtained by the preparation method according to any one of claims 6 to 10.

13. A method for deolefination of aromatic hydrocarbons, comprising: The aromatic material is contacted with the modified calcium-based montmorillonite according to any one of claims 1 to 5 or the modified calcium-based montmorillonite prepared by the method according to any one of claims 6 to 10 or the aromatic deolefination catalyst according to claim 12 to remove olefins from the aromatic material; Preferably, the contact reaction conditions include: temperature of 150-270°C, pressure of 0.6MPa-3.0MPa, feed weight space velocity of 2-8h -1 .